The Canadian Historical Association’s Presidential Addresses, 1922–2022 - Wright, Donald (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2023)
On the occasion of the Canadian Historical Association’s centenary, this article surveys continuity and change in 100 years of presidential addresses. Using Penny Bryden’s idea of the nets we weave as historians to research and write history — an idea she developed in her 2021 presidential address — I reflect on my own net, how it has changed, and what it caught in reading every presidential address since 1922: national unity, limited identities, historiography, biography, Indigenous history, and the purpose of a professional association.